The theme of life in Los heraldos negros by César Vallejo - Caballero Alayo, Carlos (Espergesia, 2018)
The objective of this work is to highlight the allusions to life in the poems Los Heraldos Negros by César Vallejo. From his poetic creations it is possible to understand what the “vate” thought about the very origin of life, his feelings for his own life and what ideals he had for the lives of others. Reading his poetry and selecting some of his texts, we came to the conclusion that he was a religious man, but at the same time sympathetic to Marxist ideals, hence his dialectical conception embodied in some poetic texts of his European stay. In our work we comment on poetic texts that reveal their feelings towards other people’s lives. Love, solidarity, interest for the needy are the feelings we find in this poetry that transcends time and space.